Has translation gone online and collaborative?: An experience from Minna no Hon’yaku - Kageura, Kyo; Abekawa, Takeshi; Utiyama, Masao; Sagara, Miori; Sumita, Eiichiro (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
We have been running Minna no Hon'yaku (MNH: Translation of/by/for all), an open online translation hosting and translation-aid service, since April 2009, with use by NGOs specifically in mind. We subsequently started two sibling services, i.e. Ryugakusei Net @ MNH, a commercial "crowdtranslation" site, in March 2010, and Kotoba no Volunteer @ MNH, a project for collecting and making available expressions useful in disaster and post-disaster situations in different languages, in May 2011. This paper aims first to introduce basic features of these three systems and their state of usage, and second, to clarify the nature of activities being carried out using these systems and the relationships between the nature of activities and various factors that contribute to shaping the activities. While what is discussed is based mainly on the insights we have obtained from our experience designing, developing and running these systems, we attempt to situate the observation within a general framework discussion of online and/or collaborative translation.